2004
DOI: 10.1111/j.1600-0684.2004.00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in hematology, biochemical values, and restraint ECG of rhesus monkeys (Macaca mulatta) following 6‐month laboratory acclimation

Abstract: The aim of this study was to determine if 6-month acclimation would enable accurate evaluation of hematological, biochemical data, and ECG recorded under restraint for conscious rhesus monkeys of both sexes. Periodic evaluation of these parameters was made during the 6-month period of acclimation. The platelet count, alkaline phosphatase, glucose, and sodium levels significantly decreased, whereas creatinine increased, compared with pre-acclimation values. The heart rate was significantly reduced compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
27
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 29 publications
11
27
2
1
Order By: Relevance
“…When evaluating hematological changes in rhesus monkeys after a 6-mo laboratory acclimatization, individuals adapted to the laboratory routine and human presence and manipulation, and had lower leukocyte counts due to preacclimatization (Hassimoto et al 2004) vs. individuals that were not acclimatized, which suggests that restraint-adapted individuals show lower stress-related effects in their leukocyte counts and could account for the higher leukocyte values in our sample vs. values in captives.…”
Section: Resultsmentioning
confidence: 73%
“…When evaluating hematological changes in rhesus monkeys after a 6-mo laboratory acclimatization, individuals adapted to the laboratory routine and human presence and manipulation, and had lower leukocyte counts due to preacclimatization (Hassimoto et al 2004) vs. individuals that were not acclimatized, which suggests that restraint-adapted individuals show lower stress-related effects in their leukocyte counts and could account for the higher leukocyte values in our sample vs. values in captives.…”
Section: Resultsmentioning
confidence: 73%
“…As expected, we found that pre and postdose measurements were generally well correlated across individuals, supporting the utility of normalization of postdose measurements to predose measurements per subject. We also found that multiple blood measurements, including hematocrit, were significantly decreased after a single dose of PBS or of placebo siRNA-LNP as described [33]. Data from paired PBS and placebo siRNA-LNP treated rhesus in nine studies were pooled and examined for changes in hematocrit (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 98%
“…S1. This effect has been well documented in rhesus and is believed to be related to changes in respiratory rate and blood pressure caused by either physical restraint or anesthesia [33]. In order to prevent masking of the phenotype caused by this stress response, especially at the lowest siRNA dose, we normalized the data from hemoglobin (Hb) and hematocrit (Hct) endpoints against the placebo siRNA.…”
Section: Dose-dependent Erythropoiesismentioning
confidence: 99%
“…Five millimolar p-toluenesulfonic acid was used as a mobile phase isocratically at a flow rate of 0.8 ml/min. Creatinine and trimethylamine The creatinine contents of the fermented fish and bean pastes were measured by the creatininase-F-DAOS method [8] using a Determiner L-CRE test kits (Kyowa Medex, Kyoto, Japan). Trimethylamine was determined by the picrate method [9].…”
Section: Methodsmentioning
confidence: 99%